2021
DOI: 10.3389/fbioe.2021.759016
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Localization of Exogenous Cry1Ab/c and its Interaction with Plasma Membrane Ca2+-ATPase in Transgenic Rice

Abstract: The cellular localization of exogenous proteins expressed in transgenic crops not only determines their stability, but also their effects on crop growth and development, including under stressful conditions; however, the underlying molecular mechanisms remain unknown. Here, we determined the cellular distribution of exogenously expressed Cry1Ab/c protein in insect-resistant transgenic rice Huahui-1 (HH1) cells through subcellular localization, immunohistochemistry, immunofluorescence, and western blot analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This interaction was shown to affect the localization and activity of Ca 2+ ‐ATPase, particularly under salt stress. Transgenic HH1 plants exhibited reduced Ca 2+ ‐ATPase activity and adverse growth effects, including decreased height and biomass, especially under salt stress 46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction was shown to affect the localization and activity of Ca 2+ ‐ATPase, particularly under salt stress. Transgenic HH1 plants exhibited reduced Ca 2+ ‐ATPase activity and adverse growth effects, including decreased height and biomass, especially under salt stress 46 …”
Section: Discussionmentioning
confidence: 99%
“…Transgenic HH1 plants exhibited reduced Ca 2+ -ATPase activity and adverse growth effects, including decreased height and biomass, especially under salt stress. 46 There have been studies investigating the uptake of Cry proteins by plants from the soil. One such study 47 focused on the absorption, translocation, and effects of Cry1Ac peptides from transgenic cotton to intercrops.…”
Section: Seedling Dry Weightmentioning
confidence: 99%
“…Activation of SOS1 under salt stress requires activation of SOS2 (an serine/threonine-protein kinase) and the establishment of a proton gradient generated by H + -ATPase in the plasma membrane ( Haruta and Sussman, 2012 ). The interaction between the plasma membrane Ca 2+ -ATPase and Cry1Ab/c may affect the salt resistance of the transgenic rice line ‘Huahui-1’ (‘HH1’) by reducing Ca 2+ -ATPase activity under salt stress ( Fu et al., 2021 ). The candidate gene LOC_Os11g29490 identified in the present study encodes a plasma membrane ATPase, and a single A to G mutation (at chr11:17109866) in the exon caused significant changes in GP between different haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, the intracellular Cry1Ab/Cry1Ac protein was found to interact with endogenous florigen Hd3a that resulted in delayed heading in rice, 17 and interact with plasma membrane Ca 2+ -ATPase that caused reduction of plant height and biomass. 18 Theoretically, the interaction of foreign Bt proteins with endogenous proteins is inevitable; in reality, the unintended effects resulting from exogenous protein accumulation in cells gradually have been discovered and disclosed. Thus, on the weight of evidence, there is limitation to the current strategy for developing Bt crops and even GM crops.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that the Bt protein Cry1Ab/Cry1Ac could bind to the proteins related to photosynthesis and stress resistance, or small molecules in the cytoplasm or nucleus 16 . Furthermore, the intracellular Cry1Ab/Cry1Ac protein was found to interact with endogenous florigen Hd3a that resulted in delayed heading in rice, 17 and interact with plasma membrane Ca 2+ ‐ATPase that caused reduction of plant height and biomass 18 . Theoretically, the interaction of foreign Bt proteins with endogenous proteins is inevitable; in reality, the unintended effects resulting from exogenous protein accumulation in cells gradually have been discovered and disclosed.…”
Section: Introductionmentioning
confidence: 99%